Diffusion Across International Organizations: Connectivity and Convergence. (15th November 2018) - Sommerer, Thomas; Tallberg, Jonas
Abstract: While extensive research shows that policies and institutions spread across states through processes of diffusion, we know little about diffusion among international organizations (IOs). We develop a novel approach for the study of diffusion among IOs. This approach consists of three components: a theoretical focus on connectivity among IOs as pathways for diffusion; a conceptual differentiation between alternative types of convergence effects; and a methodological strategy combining dyadic and spatial analysis of diffusion. We illustrate the usefulness of this approach through an empirical case: the diffusion of participatory governance arrangements among IOs from 1970 to 2010. The analysis shows that connectivity among IOs contributes to convergence, which typically is manifested through imitation of very specific institutional models. The article's findings have implications both for the study of IOs and for the general study of diffusion.